Supplementation of dietary areca nut extract modulates the growth performance, cecal microbiota composition, and immune function in Wenchang chickens - Wang, Shiping; Wang, Hong; Jiang, Qicheng; Dai, Jiahui; Dai, Wenting; Kang, Xiaoning; Xu, Tieshan; Zheng, Xinli; Fu, An; Xing, Zengyang; Chen, Yiyong; He, Zhongchun; et al. (Frontiers in Veterinary Science, 2023)
The study was aimed at evaluating the effects of areca nut extract (ANE) on the growth performance, cecal microbiota, and immunity of Wenchang chickens. For this study, 42-day-old healthy Wenchang chickens (n = 450) with similar body weight were chosen. The animals were randomly divided into five groups, with six replicates per group and 15 chickens per replicate. One group was fed a basal diet (control; CCK). The remaining four groups were fed a basal diet supplemented with varying ANE concentrations: 0.038, 0.063, 0.100, and 0.151 g/kg, with the groups denoted as CNT1, CNT2, CNT3, and CNT4, respectively. The feeding experiment lasted 35 days. The ligated cecum segments of the control and experimental groups were collected for metabolomic and metagenomic analysis, while the bone marrow samples were extracted for tandem mass tag (TMT)-based proteomic analysis. All the experimental groups exhibited significantly higher average daily gain (ADG) and significantly lower feed-to-weight (F/G) ratios than CCK. Metabolomic screening of the cecum contents revealed the presence of 544 differential metabolites, including several gut health–related metabolites, such as xanthine, hydroxy hypoxanthine, 2,5-dimethylhydrazine, ganoderic acid, and 2-aminohexanoic acid. Metagenomic analysis of the cecum contents showed an upregulation in the abundance of Prevotella spp. in the experimental groups. However, we observed no significant differences in the abundances of other cecal microbes at phylum and genus levels. Furthermore, we observed significant associations between Prevotella spp. and the differentially abundant metabolites, such as cherubins, thiaburimamide, and 3,4-dihydroxy-L-phenylalanine, (r)-mevalonate, 5-O-methylalloptaeroxylin, nalidixic acid, and deoxyloganin (P < 0.05). Proteomic analysis revealed that the differentially expressed proteins (such as interferon-induced protein with tetratricopeptide repeats 5 (IFIT5), MHC-BF1, and death domain-associated protein (Daxx)) in the bone marrow of the chickens were primarily enriched in the immune network for IgA production and B cell receptor signaling pathway. In conclusion, dietary ANE supplementation was found to enhance metabolic activity and energy utilization, improve growth performance, modulate cecal microbiota, and strengthen the immunity of Wenchang chickens.